2017
DOI: 10.1007/s00436-017-5386-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Echinococcus granulosus isolates from Bulgarian human cystic echinococcosis patients

Abstract: Although cystic echinococcosis (CE) is highly endemic in Bulgaria, there is still scarce information about species and/or genotypes of the Echinococcus granulosus complex that infect humans. Our study tackled the genetic diversity of E. granulosus complex in a cohort of 30 Bulgarian CE patients. Ten animal E. granulosus isolates from neighboring Greece were additionally included. Specimens were comparatively analyzed for partial sequences of five mitochondrial (mt) (cox I, nad I, rrnS, rrnL, and atp6) and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…This genetic form was found in sheep, cattle and pig in the country, whereas the present fi nding provides the fi rst report of G3 in humans from Romania. High rates of G3 infections within E. granulosus s.s. were recently recorded also in neighboring Serbia (40 %, 18 of 40 isolates) and Bulgaria (46.7 %, 14 of 30 isolates) (Debeljak et al, 2016;Marinova et al, 2017). Interestingly, in two of the four human samples E. canadensis G7 was diagnosed as CE causative agent.…”
Section: Discussionmentioning
confidence: 74%
“…This genetic form was found in sheep, cattle and pig in the country, whereas the present fi nding provides the fi rst report of G3 in humans from Romania. High rates of G3 infections within E. granulosus s.s. were recently recorded also in neighboring Serbia (40 %, 18 of 40 isolates) and Bulgaria (46.7 %, 14 of 30 isolates) (Debeljak et al, 2016;Marinova et al, 2017). Interestingly, in two of the four human samples E. canadensis G7 was diagnosed as CE causative agent.…”
Section: Discussionmentioning
confidence: 74%
“…Although formerly known as the “buffalo strain”, E. granulosus s.s. G3 has a wide range of intermediate hosts and is now recognized to circulate in almost all continents [ 15 , 36 ]. It is significantly less prevalent worldwide than genotype G1 but was found to be associated with a high rate of human CE cases in Italy, Bulgaria, Pakistan, Iran and India [ 37 , 38 , 39 , 40 , 41 ]. Until recently, it was not possible to differentiate unambiguously between genotypes G1 and G3, so the real contribution of genotype G3 to the global burden of CE may have been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Fragments of cytochrome c oxidase subunit 1, cox1 [ 38 ], NADH dehydrogenase subunit 1, nad1 [ 38 , 54 ], NADH dehydrogenase subunit 5, nad5 [ 55 ] and small ribosomal RNA, rrnS [ 55 , 56 ] mitochondrial genes were amplified by conventional PCR as described previously, using FastStart™ High Fidelity PCR System (Roche, Germany) reagents. The sequences of the primers are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The results presented in this report indicated that G1 was the most dominant distinct species of E. granulosus s. s. in the hydatid cyst samples from humans and animals in regions of the QTPA, China. The epidemiological data of this present study were in line with some previous molecular studies from China that had demonstrated G1 was the most common and dominant species of E. granulosus s. s. in humans, livestock and wild animals in China (Ma et al ., 2008, 2015; Yang et al ., 2009; Liu et al ., 2013; Yan et al ., 2013; Zhong et al ., 2014; Hu et al ., 2015), Turkey (Erdogan et al ., 2017), Iran (Farhadi et al ., 2015; Arbabi et al ., 2017), and Bulgaria (Marinova et al ., 2017). Likewise, many epidemiological studies conducted in the majority of regions of the world have also indicated E. granulosus s. s. G1 as the predominant species (Laurimae et al ., 2016; Roinioti et al ., 2016; Avila et al ., 2017; Debiaggi et al ., 2017; Ehsan et al ., 2017; Thapa et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis employing mitochondrial genes ( cox 1, nad 1, cob and nad 5 gene) and ribosomal genes might reveal the biological relationships between Echinococcus spp. and strains (Marinova et al ., 2017; Kinkar et al ., 2018 a ). Mitochondrial DNA (mtDNA) is the most suitable genetic marker for the analysis of genetic diversity, genetic differentiation and evolution of species and is widely used in species classification (Umhang et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%